Information Trustworthiness and Information Adoption in Social Media Marketing: Contextualization of Ewom and Its Implications For Marketers - Sulistiyani; Frans Sudirjo (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Social media platforms have exposed consumers to a large amount of either accurate information or misleading information. The quick spread of information through electronic word-of-mouth on social media networks has made it difficult for consumers to distinguish between marketer-generated content and user-generated content. This study aims to identify the factors that influence consumers when making purchasing decisions and to establish a comprehensive framework for consumers in the digital marketing. The study aimed to investigate how technology acceptance, electronic word-of-mouth (eWOM), and perceived risk affect information adoption by users in social media marketing. The study collected data from 213 social media users in Semarang via an online survey and used partial least squares structural equation modeling (PLS-SEM). The findings showed that information trustworthiness and information adoption were intermediaries between information quality, usefulness, perceived risk, argument quality, and information adoption. The study suggests that the quality and usefulness of the information are significant factors that affect the adoption of information. For social media marketers, providing high-quality and balancing useful information can increase consumer chances of adoption, thereby leading to purchase intention. The findings highlight for the marketers to ensure that the information provided is of high quality and relevant to the target audience. Keywords: digital marketing, social media, information adoption, electronic word-of- mouth, trust